Study of Optical Properties of CdS Films Prepared by Thermal Evaporation in Vacuum - Elawi, H.F.; Balwa, B.D.; Ali, H.F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
CdS films were prepared by thermal evaporation at pressure (10-6torr) of 1Î¼m thickness onto glass substrate by using (Mo) boat. The optical properties of CdS films, absorbance, transmittance and reflectance were studied in wavelength range of (300-900)nm. The refractive index, extinction coefficient, and absorption coefficient were also studied. It's found that CdS films have allowed direct and forbidden transition with energy gap 2.4eV and 2.25eV respectively and it also has high absorption coefficient (Î± >104cm-1).